Mister Lullaby a novel - Markert, James (New York, NY Crooked Lane Books, 2023)
"The small town of Harrod's Reach has seen its fair share of the macabre, especially inside the decrepit old train tunnel around which the town was built. After a young boy, Sully Dupree, is injured in the abandoned tunnel and left in a coma, the townspeople are determined to wall it up. Deputy sheriff Beth Gardner is reluctant to buy into the superstitions until she finds two corpses at the tunnel's entrance, each left with strange calling cards inscribed with old lullabies. Soon after, Sully Dupree briefly awakens from his coma. Before falling back into his slumber, Sully manages to give his older brother a message. Sully's mind, since the accident, has been imprisoned on the other side of the tunnel in Lalaland, a grotesque and unfamiliar world inhabited by evil mythical creatures of sleep. Sully is trapped there with hundreds of other coma patients, all desperately fighting to keep the evils of the dream world from escaping into the waking world. Elsewhere, a man troubled by his painful youth has for years been hearing a voice in his head he calls Mr. Lullaby, and he has finally started to act on what that voice is telling him--to kill any coma patient he can find, quickly. Something is waking up in the tunnel--something is trying to get through. And Mr. Lullaby is coming." --
112666
Keywords: Coma -- Patients -- Fiction; Nightmares -- Fiction; Murderers -- Fiction; Coma -- Patients -- Romans, nouvelles, etc; Horror fiction; Novels; Romans